2000
DOI: 10.1103/physrevd.61.072005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement ofsin2βfromBJ/ψK

Abstract: This paper reports an updated measurement of the standard model CP violation parameter sin 2␤ using the CDF Detector at Fermilab. The entire run I data sample of 110 pb Ϫ1 of proton-antiproton collisions at ͱs ϭ1.8 TeV is used to identify a signal sample of ϳ400 B→J/ K S 0 events, where J/→ ϩ Ϫ and K S 0 → ϩ Ϫ. The flavor of the neutral B meson is identified at the time of production by combining information from three tagging algorithms: a same-side tag, a jet-charge tag, and a soft-lepton tag. A maximum like… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 36 publications
9
111
0
Order By: Relevance
“…Depending on the slepton type, their masses, if they exist, must be larger than about 85 GeV (for staus) to 100 GeV/c 2 (for selectrons). Exclusion limits for sleptonquark and gluion production, from the combined four LEP experimen and the Tevatron experiments [16,17].…”
Section: Current Limits From Particle Accelerator Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the slepton type, their masses, if they exist, must be larger than about 85 GeV (for staus) to 100 GeV/c 2 (for selectrons). Exclusion limits for sleptonquark and gluion production, from the combined four LEP experimen and the Tevatron experiments [16,17].…”
Section: Current Limits From Particle Accelerator Experimentsmentioning
confidence: 99%
“…The most stringent mass limits for squarks and gluinos are provided both by the LEP experiments [16] and by the CDF and the D0 experiments at the Tevatron [17]. Again, no positive signals were seen, leading to the exclusion limits summarised in Fig.…”
Section: Current Limits From Particle Accelerator Experimentsmentioning
confidence: 99%
“…Dominant background is QCD heavy flavour production with other contributions from fake triple tags, t t t and W=Z þ jets. Direct searches from CDF [103] look for H þ ! tn using t identification via its hadronic decays and they thus are sensitive only in the large tan b region.…”
Section: 2mentioning
confidence: 99%
“…CDF and D0 are now scheduled to turn on in 2001. CDF already has shown that it has the potential to measure CP in J/ψK S [42], and promises to measure B s mixing.…”
Section: Future Experimentsmentioning
confidence: 99%